2020
DOI: 10.1101/2020.07.22.20159251
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exome sequencing identifies rare damaging variants in ATP8B4 and ABCA1 as novel risk factors for Alzheimer’s Disease

Abstract: Background: With the development of next-generation sequencing technologies, it is possible to identify rare genetic variants that influence the risk of complex disorders. To date, whole exome sequencing (WES) strategies have shown that specific clusters of damaging rare variants in the TREM2, SORL1 and ABCA7 genes are associated with an increased risk of developing Alzheimers Disease (AD), reaching odds ratios comparable with the APOE-ε4 allele, the main common AD genetic risk factor. Here, we set out to iden… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

7
2

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 77 publications
2
40
0
Order By: Relevance
“…In locus 13, among the 4 genes, NDUFAF6 exhibited the highest number of hits but TP53INP1 was also of interest. In locus 21, a recent report pointing to an increased burden of rare variants in ATP8B4 in AD patients prioritizes this gene 28 . For the locus 29, we consider LILRB2 as a plausible risk gene according to bibliographical data 29,30 .…”
Section: Resultsmentioning
confidence: 99%
“…In locus 13, among the 4 genes, NDUFAF6 exhibited the highest number of hits but TP53INP1 was also of interest. In locus 21, a recent report pointing to an increased burden of rare variants in ATP8B4 in AD patients prioritizes this gene 28 . For the locus 29, we consider LILRB2 as a plausible risk gene according to bibliographical data 29,30 .…”
Section: Resultsmentioning
confidence: 99%
“…However, segregation data of SORL1 variants remains very scarce, not allowing to assess their mode of inheritance. We showed that such variants are enriched in EOAD cases with a positive family history in a case-control study, with exome-wide significance 5 , and such results were subsequently extended to all AD cases with a clear effect on ages at onset [6][7][8] . Given the extreme rarity of premature termination codon-introducing variants in controls and very high odds ratios 6 , the question of the penetrance of such variants and a putative use for genetic counseling has been raised.…”
Section: Introductionmentioning
confidence: 56%
“…There were multiple variants with ADSP.P-values < 0.05 in TREM2 (4) and RIN3 (2), two genes previously associated with AD and in ATP8B4 (3) and IL17RA (2). Neither ATP8B4 nor IL17RA were linked to AD by the AD GWAS performed to date 20,24,25 , but Holstege, et al 26 recently reported that carrying rare damaging variants in ATP8B4 is associated with AD.…”
Section: Discussionmentioning
confidence: 99%